Oil, Transitions, and the Blue Economy in Canada - Leah M. Fusco; Marleen S. Schutter; Andrés M. Cisneros-Montemayor (Sustainability, 2022)
Decisions about whether to include oil in blue economy plans can be controversial but also fundamental to the ability of these plans to transform (or not) business-as-usual in the oceans. This paper examines (a) how oil is sometimes included and justified in blue economy planning when its development is at odds with climate commitments and the need for just transitions away from fossil fuels, and (b) how oil could be included in blue economy planning, or transitions to blue economies and just energy transitions away from oil. We examine how tensions between sustainability/climate commitments and oil development impacts are resolved in practice, specifically by analyzing a particular approach to the blue economy that focuses on technology and innovation. The overlap of oil with renewable energy, specifically through technology, has become an important part of recent ocean and blue economy narratives in oil-producing nations and illustrates the contradictions inherent in ocean development discourse. We draw specifically on the case of Newfoundland and Labrador (NL), the only province in Canada with a mature offshore oil industry and thus the region most potentially impacted by decisions about whether to include oil in Canada’s blue economy. We argue that the blue economy approach to ocean governance being enacted in NL is currently being used as a form of legitimation for continuing the development of oil with no real transition plan away from it. Furthermore, we argue that blue economy plans must not only envision transitions to renewables but also explicitly and actively transitions away from oil to minimize environmental and social justice and equity issues at multiple scales. We end by highlighting some necessary conditions for how ocean economies that include oil can transition to sustainable and equitable blue economies.